The Dynamics of Indonesian Consumption Patterns of Rice and Rice-Based Food Eaten Away From Home - Saliem, Handewi Purwati; Hermanto, nFN; Suryani, Erma; Suhaeti, Rita Nur; Ariani, Mewa (Analisis Kebijakan Pertanian, 2023)
As a major staple food for most of the Indonesian population, rice has an important position in term of social, economic, and political aspects in the country. Because of that position, it is important to identify rice consumption pattern of Indonesian people. This research aims at analyzing the trends of rice consumption at home and rice-based eaten away from home in terms of weight and expenditure. By using mathematical and simple statistical methods, data of household rice consumption from National Socio-economic Survey (Susenas) years 1996 to 2017 (seven data sets) were analyzed by location and income quintiles. Results of these analyses indicated that during 1996 to 2017 the real expenditure of food away from home tended to increase, the real expenditure and per capita of rice consumption for all household categories tended to decrease, and the expenditure for processed rice had different path compared to the expenditure for rice consumption. The implication of this study is the estimation of national demand for rice should consider the amount of rice eaten away from home consumption and also processed rice. AbstrakSebagai makanan pokok hampir seluruh penduduk, beras menempati posisi penting dari sisi sosial, ekonomi, dan politik di Indonesia. Berdasar hal tersebut, penting untuk mengidentifikasi pola konsumsi beras penduduk Indonesia. Penelitian ini bertujuan untuk menganalisis laju konsumsi beras yang dimakan di rumah maupun di luar rumah berupa makanan jadi berbasis beras baik dari sisi pengeluaran maupun jumlahnya. Dengan menggunakan metode matematika dan statistika sederhana, penelitian ini mengolah data Susenas tahun 1996−2017 (tujuh set data) dengan membedakan konsumsi rumah tangga menurut lokasi (desa-kota) dan kuintil. Hasil penelitian menunjukkan bahwa selama 1996−2017 pengeluaran riil untuk makanan jadi cenderung meningkat, pengeluaran riil dan konsumsi beras per kapita cenderung menurun untuk semua kategori rumah tangga, dan pengeluaran untuk pangan olahan berbasis beras memiliki pola yang berbeda dengan pengeluaran untuk konsumsi beras. Implikasi dari penelitian ini adalah bahwa dalam mengestimasi kebutuhan beras nasional perlu mempertimbangkan jumlah konsumsi beras yang dimakan di luar rumah dan pangan olahan berbasis beras.
Keywords: beras; dinamika pola konsumsi; pengeluaran untuk pangan; konsumsi di luar rumah; consumption pattern dynamics; eaten away from home; food expenditure; rice